(untitled) (Journal of Hama University, 2020)
The study was carried out on 30 sexually mature male rabbits aged 6 months with an average weight of 1600 gm from a local breed. The study aimed to investigate the effect of adding Eruca sativa mature seeds in different proportions with the forage mixture provided on some reproductivity indicators. The study was conducted on semen to measure the collective motility and the percentage of malformation sperm, in addition to measure the level of testosterone in blood. Three groups were employed, with six rabbits in the control group and 24 rabbits in the other groups, each for 12 rabbits. The control group was given water and a balanced fodder mix while the other study groups were fed on a balanced fodder mix with Eruca sativa seeds. (group 1 was given (%3)/Kg of fodder while group 2 was given (%6)/Kg of fodder) and the study lasted for 30 days. The samples were obtained in two phases after 15 and 30 days. The results revealed a non-significant increase in the percentage of sperm motility in group 1 and group 2 compared with each other and compared with the control group in the two phases (15, 30) days. A significant decrease (p<0.05) was noticed in the percentage of sperm malformation in group2 compared to the control group and group1 during the first phase after 15 days. As such results in the second phase after 30 days showed a significant decrease (p<0.05) in the percentage of sperm malformation in group 1 and 2 in comparison with them and in comparison with the control group. The results of the study also showed a significant increase (p<0.05) in the stage after 15 days in the level of Testosterone concentration in blood plasma in group 2 compared with the control group. A significant increase (p<0.05) was observed after 30 days in group1 compared to the control group, while a significant increase (p<0.05) was observed in group 2 compared with the control group and group1.